Kesejahteraan Masyarakat Desa Fatufia Kecamatan Bahodopi Kabupten Morowali: (Studi Kasus Penduduk Asli dan Penduduk Pendatang) - Marwani; Saputra, Iwan Alim (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2023)
The aim of the study was to describe and determine the welfare of the residents of Fatufia Village, Bahodopi District, Morowali Regency (Case Study of Indigenous and Migrant Populations). This type of qualitative research uses a descriptive approach. Data collection techniques using observation, interviews, and documentation. The data analysis techniques performed were data reduction, data presentation, and data verification. The results of the study show that: 1) Welfare from the economic condition factor of the residents in Fatufia Village can be said to be quite prosperous because they have an income of IDR 3,000,000 to IDR 7,000,000 in one month. Meanwhile, expenses in one month can be fulfilled. Welfare from the conditions of residence for residents in Fatufia Village for the original occupation and occupation can be said to be quite good. 3) The welfare of the community can be measured by the condition of the facilities where the residents in Fatufia Village live, both natives and immigrants are quite good. 4) For the factor of increasing the social welfare of the residents of Fatufia Village, on average they work for companies located in Fatufia Village, so it can be said that they are already good. So the welfare of the people in Fatufia Village, both natives and immigrants, is quite good and quite prosperous.